Using Analytical Hierarchy Process Integrated With Geographic Information System and Remote Sensing (AHP/GIS/RS) For Mapping Groundwater Potentiality in West El-Minia Area, Upper Egypt (Journal of Nuclear Technology in Applied Science, 2021)
Water resources management is considered a major socio-economic issue and a central component for future development; this implies an increasing demand for exploration of groundwater of high potentiality to cope with the excessive needs. In this work, Analytic Hierarchy Process (AHP) which is a widely used Multi- Criteria Decision Analysis (MCDA) has been used with Geographic Information System and Remote Sensing for classifying and mapping zones that intrinsically control and reflect groundwater potentiality in the western area of El Minia Governorate, Upper Egypt. Six parameters of high attributes to groundwater recharge potentiality (Geology, Geomorphology, Slope, Lineaments Density, Drainage Density, and land use/land cover) have been selected. Assigned weights based on their relative importance to groundwater recharge, the weights were compared in a pair-wise matrix, the Eigen values were determined and the consistency ratio was calculated to validate the assigned weights; the ranges of these parameters are classed and rated. Overlay analysis was done to integrate the thematic layers of the parameters in Arc GIS domain for the development of a groundwater recharge potential map which has been verified using stable isotopic content (δ18O and δD) of 67 groundwater samples collected from the study area. Three groundwater potentiality zones; (high, intermediate and low) have been delineated in a recharge potentiality map. The demarcated zones numerically integrate the geological hydrogeological and anthropogenic impacts on groundwater recharge and introduce a base for sustainable development of groundwater in the study area
Keywords: Groundwater recharges Potentiality; Analytic Hierarchy Process; ArcGIS/RS; Environmental Stable Isotopes; El Minia